Monitoring urban river water quality using macroinvertebrate and physico-chemical parameters: Case study of Penchala river, Malaysia - Mahazar A.; Shuhaimi-Othman M.; Kutty A.A.; Mohamed Desa M.N. (2023)
A study have been carried on urban river, Sungai Penchala to assess the river water quality by using benthic macroinvertebrates as biological indicator and also standard Department of Environment (DOE) water quality measurement for physical-chemical analysis of Water Quality Index (WQI). Sampling for benthic macroinvertebrate and water sample was done on 3 sampling sites, named upstream (SI), middle stream (S2) and downstream (S3). The benthic macroinvertebrate sampling was done in the same day at the same place the water samples were collected in 5 replicates, while the water samples were collected in 3 replicates for each river section. The benthic macroinvertebrates was sampled using Surber's net and water measurement for dissolved oxygen, temperature, pH and conductivity was measured in-situ using HYDROLAB Quanta, multi-parameter water quality instrument. Collected water sample was transferred to laboratory for measurement of total suspended solid, BOD5, chemical oxygen demand and ammoniacal nitrogen. The result from the assessment show that Sungai Penchala is classified as having good water quality on the upstream section but the water quality distorted in the middle and downstream section based on WQI and BMWP score. Non-parametric test of Kruskal-Wallis test show that most water parameter are significantly differ among river section (p>0.05, ? = 0.05). 2013 Asian Network for Scientific Information.